Neonatal acute limb ischemia - Rebecca Bonny-Obro; Yapi Landry Aké; Kokoe Midekor-Gonebo; Amenan Kan Kouassi-Dria; Sigue Jean Ouattara; Moufidath Sounkere-Soro; Kokora Xavier Dibi; Ello Nicolas Moh (Elsevier, 2021)
Acute limb ischemia is a rare disorder in the perinatal period. The etiology and management of acute limb ischemia is not well described. We report 4 cases of acute limb ischemia in the neonatal period. Observations: We present the cases of four premature neonates aged between 6 and 15 days. The mothers of one of the neonates had a history of gestational diabetes. Three neonates were born by eutocic vaginal delivery and one, by cesarean section. Reasons for hospitalization of the neonates included infections (3 cases), hyaline membrane disease (2 cases) and congenital malaria (1 case).The neonates presented with cyanosis localized in the fingers (1 case), cyanosis on the fingers extending to the forearm (2 cases) and cyanosis localized in the toe (1 case). All patients had a peripheral intravenous catheter implanted in the affected limb. In three cases, there was an infectious syndrome and in one case, hemostasis was impaired. Doppler ultrasound of the blood vessels in the affected limb revealed arterial thrombosis in 2cases. Management involved antibiotics, heparin therapy and fasciotomy. During hospitalization, 1 patient had spontaneous distal phalanx amputation, 1 required surgery for forearm segmental gangrene and 2 died. Conclusion: Neonatal acute limb ischemia is rare but can be fatal due to functional and vital repercussions. Treatment outcomes depend on early diagnosis, etiology and treatment.